An Algorithm for Computing Spline Function - K.H, Faraidun; Jwamer, Karwan H.F; Mohammed, Sabah Ali (Sulaimani Journal for Pure and Applied Sciences, 2016)
A numerical algorithm is constructed to develop numerical solution to the spline function based belonging to theC6-class. The presented method showed that the approximate solution for boundary value problems obtain by the numerical algorithm which are applied sixticspline function is effective. Convergence analysis of the proposed method and error estimates are obtained. Numerical results illustrate by two examples are given the practical usefulness and efficiency of the algorithm.
Keywords: Algorithm spline interpolation; error optimality; approximate solution; convergence analysis